Effect of prolonged general anesthesia with sevoflurane and laparoscopic surgery on gastric and small bowel propulsive motility and pH in dogs. (15th October 2013) - Boscan, Pedro; Cochran, Shannon; Monnet, Eric; Webb, Craig; Twedt, David
Abstract Objective To determine if general anesthesia with sevoflurane and laparoscopic surgery changed gastric and small bowel propulsive motility or pH in dogs. Study design Prospective, controlled trial. Animals Twelve, 19–24 months old, female, Treeing Walker Hound dogs, weighing 23–30 kg. Methods Dogs were anesthetized for a median of 8.5 hours during another study to determine the minimum alveolar concentration of sevoflurane using a visceral stimulus. Gastric and small bowel motility were determined using a sensor capsule that measures pressure, pH and temperature. Gastric transit time and motility index were calculated. For 8/12 dogs, gastric motility, pH and transit time were measured. In 4/12 dogs, small bowel motility and pH were measured. Results Anesthesia decreased gastric and small bowel motility but did not change luminal pH. Mean gastric contraction force decreased from median (range) 11 (8–20) to 3 (1–10) mmHg (p < 0.01) and gastric motility index decreased from 0.63 (0–1.58) to 0 (0–0.31; p = 0.01). Frequency of contractions did not change, 3.7 (1.6–4.4) versus 2.8 (0.1–5.1) contractions minute−1 (p = 0.1). Gastric motility returned to normal 12–15 hours following anesthesia. Gastric emptying was prolonged from 12 (5.3–16) to 49 (9.75–56.25) hours (p < 0.01). Mean small bowel contraction force decreased from 34 (24–37) to 3 (0.9–17) mmHg (p < 0.02) and motility index decreased from 3.75 (1–4.56) to 0 (0–1.53; p = 0.02). Frequency of contractions did not change, 0.5 (0.3–1.4) versus 1.4 (0.3–4.6) contractions minute−1 (p = 0.11). Small bowel motility returned within 2 hours after anesthesia. Laparoscopy did not result in changes to gastric or small bowel parameters beyond those produced by general anesthesia. Conclusions and clinical relevance The force of gastric and small bowel contractions decreased during sevoflurane anesthesia for laparoscopy. Although gastric motility returned to normal within 12–15 hours the impairment of gastric emptying lasted 30–40 hours, predisposing dogs to postoperative ileus.